2018
DOI: 10.3389/fneur.2017.00721
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Factor VIII and von Willebrand Factor Levels Predict Unfavorable Outcome in Stroke Patients Treated with Intravenous Thrombolysis

Abstract: IntroductionPlasma factor VIII (FVIII) and von Willebrand factor (VWF) levels have been associated with the rate and severity of arterial thrombus formation and have been linked to outcomes following thrombolytic therapy in acute myocardial infarction patients. Here, we aimed to investigate FVIII and VWF levels during the course of thrombolysis in acute ischemic stroke (AIS) patients and to find out whether they predict long-term outcomes.Materials and methodsStudy population included 131 consecutive AIS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
1
34
1
2
Order By: Relevance
“… 4 While studies show a correlation of elevated factor VIII with thrombotic events, our case depicts a severe care of TS due to elevated factor VIII associated thrombotic coagulopathy. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 4 While studies show a correlation of elevated factor VIII with thrombotic events, our case depicts a severe care of TS due to elevated factor VIII associated thrombotic coagulopathy. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding ischemic stroke patients who underwent thrombolysis, a study found that having elevated FVIII levels, both immediately and 24 hours after thrombolysis, led to a higher risk for poor functional outcome (mRS ≥ 3) at 90 days. 25 There have been some important recent developments regarding hemostatic factors in the context of first stroke that may also inform future treatment strategies in the context of secondary prevention. For instance, FXI appears to be a stronger risk factor for first ischemic stroke than myocardial infarction 26 and may therefore be a particularly attractive target.…”
Section: Discussionmentioning
confidence: 99%
“…As at the time of patient enrollment mechanical thrombectomy was not yet available, none of the patients received such treatment. Baseline characteristics of the patient cohort have been published earlier . The presence of IS was diagnosed based on clinical symptoms, brain imaging using non‐contrast computerized tomography (NCCT) scan, and CT angiography (CTA).…”
Section: Methodsmentioning
confidence: 99%